Assessing skin pigmentation in epidemiological studies: The reliability of measurements under different conditions. Issue 2 (29th December 2012) - Uter, W.; Benz, M.; Mayr, A.; Gefeller, O.; Pfahlberg, A.
<x xml:space="preserve">Abstract</x> Background/purpose Different devices are used for the non‐invasive measurement of (constitutive) skin pigmentation in (epidemiological) studies. Reproducibility of measurements with the Chromameter (CM, model CR 300, Minolta, Osaka) and the Reflectometer (RM, Courage & Khazaka, Cologne) has not yet been examined in detail and was addressed in a set of four experiments and studies respectively. Methods Regarding the CM, the Y value of the Yxy CIE 1931 colour system was utilized, representing lightness in this colour space, while the RM measured reflectance at 660 nm with a small bandwidth of 20 nm. Both devices measure reflectance on a scale from 0 to 100%, however, in different wavelength ranges. Between 3 and 20 repetitions were performed on standard grey scales and different sets of human volunteers, including RM measurements in a large epidemiological field study. Results While the coefficient of variation (V) increases and the intraclass correlation coefficient decreases from controlled laboratory to field conditions, reproducibility remained in a range considered acceptable, if adequate study conditions were maintained. In a direct comparison on human skin, V of the RM was significantly smaller than that of the CM. Conclusion Both devices can be used confidently in field studies; however, based on considerations of skin optics and in view of slightly lesser variability, the RM may be preferable.